'Turn-ON' furfurylamine-based fluorescent sensor for Cd2+ ion detection and its application in real water samples. (1st July 2023) - Divyashree, N.R.; Revanasiddappa, Hosakere. D.; Jayalakshmi, B.; Iqbal, Muzaffar; Amachawadi, Raghavendra G.; Shivamallu, Chandan; Prasad Kollur, Shiva
Graphical abstract: Highlights: Furfurylamine derived Schiff base ligand was prepared and used as Cd(II) probe. Tap and lake water analysis. Limit of detection was found to be 0.2345 μM. Abstract: The ability of the new furfurylamine-derived Schiff base ligand (E)-4-chloro-2-((((5-methylfuran-2-yl)methyl)imino)methyl)phenol (CFMP ) to recognize metal ions as a chemosensor has been studied. According to thorough research on the several facets of metal sensing phenomena, the Schiff base ligand CFMP demonstrated selective colorimetric and fluorescence sensing behavior towards the Cd 2+ ion in a methanol–water system with strong binding nature, which was easily visible to the human eye. Job's plot titrations were used to determine the metal–ligand complex's stoichiometry, and LCMS data served as further confirmation. The CFMP has a low detection limit (LOD) of 0.2345 µM and shown outstanding fluorescence sensing activity in buffer fluid with a pH of 7.2. Investigations into the fluorescence characteristics of the CFMP and the metal complex in the solution state revealed an improvement in fluorescence emission intensity following complexation. Additionally, utilizing electronic absorption spectroscopic techniques on samples of lake and tap water, the use of Cd 2+ ion detection in real water samples was investigated.